Effectiveness of Criminal Law Enforcement in Eradicating Corruption in National Strategic Sectors - Anis Noviya (Ipso Jure, 2026)
Corruption in national strategic sectors is a serious problem that has a broad impact on economic stability and development. This study aims to analyze the effectiveness of criminal law enforcement in eradicating corruption in national strategic sectors and to examine the influence of normative ambiguity on legal certainty. The research method used is normative legal research with a statutory, conceptual, and case approach, with primary legal material in the form of Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption in conjunction with Law Number 20 of 2001, and supported by secondary and tertiary legal materials. The results of the study indicate that the effectiveness of law enforcement is still not optimal due to normative ambiguity, particularly regarding state financial losses and abuse of authority, which gives rise to multiple interpretations and inconsistencies in law enforcement. In addition, disharmony between criminal law and state administrative law, weak coordination between institutions, and the influence of non-juridical factors such as politics and economics also hamper the effectiveness of law enforcement. The resulting legal uncertainty also impacts the investment climate and development implementation in strategic sectors. Therefore, a clearer and more assertive normative reconstruction, harmonization of regulations, and strengthening of legal structures and culture are needed to realize effective, fair law enforcement and provide legal certainty.